The Problems of Women Education in Rimba Tribe and Solutions - Anwar, K; Marmoah, S (KnE Social Sciences, 2018)
The exploitation of forest production has caused ecological crisis and undermining social order-economic-community cultural custom and indigenous forest community at Bukit Duabelas National Park (BDNP) Jambi Province Indonesia, well-known as the Rimba tribe. This critical paradigm research using case study approach aims at describing and analyzing the problem of women education of Rimba tribe in BDNP, the empowerment practices of the Rimba women, and finally providing some solutions to deal with education for Rimba women. To gather the data, the researchers occupied in-depth interviews, participatory observation, documentation studies, and field notes that were analyzed by triangulation techniques. Based on the observation and interview, the problems of women education in Rimba tribe were poverty, view of the tribe community, inequality between males and females, ignorance, early marriage, religion, custom, and culture. Therefore, the researchers came up with some solutions to overcome problems in Rimba tribe women education, terminate early marriage, empower the Rimba women, provide equal opportunity for education, change their mindset, provide scholarships, establish government policy for Rimba education, cooperate with private companies, and build a good communication with the leaders of Rimba tribe. Finally, it can be concluded that the government must be serious in designing education policy for Rimba tribe especially for women, and the Rimba tribe leader should understand how planning, organizing, leading, and controlling are applied to achieve purpose of life. Keywords: problems of women education, Rimba tribe, Jambi Province, solutions